2018
DOI: 10.1111/mcn.12664
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy density is associated with body mass index‐for‐age in Mexican adolescents

Abstract: Dietary energy density (DED) has been widely considered a risk factor for weight gain. In adolescents, however, the evidence is inconclusive, and in Mexico, the ways in which DED is associated with overweight and obesity are unknown. Our study analysed the association of DED with overweight or obesity (OW-O) in Mexican adolescents included in the National Health and Nutrition Survey 2012 (ENSANUT 2012). We analysed the data from a 7-day Food Frequency Questionnaire administered to 2,203 Mexican adolescents age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
1
9
1
Order By: Relevance
“…After adjusting for EI:BMR ratio, the direction of the associations between dietary patterns and overweight–obesity and stunting radically changed. Given the inverse correlation between BAZ and EI:BMR ratio (−0.13, p < 0.01), this may be due to underreporting of energy intake by subjects with high BAZ, which has also been suggested by a previous study in Mexican adolescents [52].…”
Section: Discussionmentioning
confidence: 76%
“…After adjusting for EI:BMR ratio, the direction of the associations between dietary patterns and overweight–obesity and stunting radically changed. Given the inverse correlation between BAZ and EI:BMR ratio (−0.13, p < 0.01), this may be due to underreporting of energy intake by subjects with high BAZ, which has also been suggested by a previous study in Mexican adolescents [52].…”
Section: Discussionmentioning
confidence: 76%
“…Past investigations examined possible mechanisms on how animal protein intake can potentially increase the risk of obesity. Although unlikely to be the single contributor to obesity, red meat and its products are energy-dense foods and this could explain their association with overweight/obesity [14,32]. Meats are frequently consumed in the western diet, particularly by adolescents, and therefore, the magnitude of the effect on their health can potentially be significant.…”
Section: Discussionmentioning
confidence: 99%
“…The development of obesity is multifactorial [13]: In general, imbalances in the diet, e.g., energy-dense diet. Several investigations on factors that contribute to childhood and adolescent obesity have focused on dietary factors [14][15][16][17][18] or habits [19][20][21][22][23]. One macronutrient that is particularly critical for normal growth and development of adolescents is protein [24], but its role in obesity development is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In this age range, underreporting generally provides lower intakes of snacks and energy-dense foods than plausible reports [ 51 ] because adolescents tend to easily forget and/or omit foods they consume [ 51 ]. Moreover, it has been documented that the exclusion of non-plausible reporters can improve the magnitude of dietary (including DED) associations with obesity [ 52 , 53 ]. Likewise, some studies have indicated that associations tend to be stronger when under-reporters are excluded from analysis or this variable is introduced as a covariate [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been documented that the exclusion of non-plausible reporters can improve the magnitude of dietary (including DED) associations with obesity [ 52 , 53 ]. Likewise, some studies have indicated that associations tend to be stronger when under-reporters are excluded from analysis or this variable is introduced as a covariate [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%